Pengaruh Program Berita “Sketsa Pemilu” Di TVRI Terhadap Persepsi Mahasiswa (Survei pada Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Jakarta Angkatan 2020 dan 2021) - Lukman, Alifia Syahradinar; Kurniawan, Donny (Educationist: Journal of Educational and Cultural Studies, 2024)
One of the mass media programs that discusses elections is the election sketch news program. The aim of the research is to measure 1). News program "Election Sketches" on TVRI, 2). Perceptions of Communication Science Students at Muhammadiyah University, Jakarta, and 3). The influence of the news program "Election Sketches" on TVRI on the perceptions of Communication Science Students at Muhammadiyah University Jakarta Class of 2020 and 2021. The theory used in this research uses the theory of news programs and student perceptions. This research also uses a quantitative approach with survey methods. Results of this research 1). The news program "Election Sketches" broadcast by TVRI has high enthusiasm among Gen Z and millennials. It is known that the influence of the "Election Sketches" news program on TVRI is classified as agreeable, with an average result of 4.25 on variable X (News Program), 2). Perception in the eyes of students is something that can be influenced, with an average value of 4.26 for variable Y (Student Perception), 3). There is an influence between the news program "Election Sketches" on student perceptions of 35.3%. while the remaining 64.7% is influenced by other factors. It is possible that the low influence of the "Election Sketches" news program on TVRI on student perceptions is due to the lack of interest of Gen Z and millennials in watching television, especially TVRI.